2022
DOI: 10.7580/kjlm.2022.46.3.71
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Age Using Nationwide Survey Data on the Number of Residual Teeth

Abstract: Given that tooth loss is a degenerative change, the number of residual teeth may be used to specify a particular age range as a marker for age estimation. This study examined changes in the number of teeth with age using a nationwide oral survey database and derived the age distribution of the Korean population according to the number of teeth. Data on the number of teeth and age were extracted from the oral examination data of the Korean National Health and Nutrition Examination Survey (KNHANES) from 2016 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The children and adults denote the number of children in the household and the number of working adults respectively. The choice of covariates in the equations is influenced by existing research (Kim & Lee, 2012; Treibich, 2015; Krause, 2019). Because of the count nature of the outcome variables, equation was estimated using Poisson regression models and marginal effects were reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The children and adults denote the number of children in the household and the number of working adults respectively. The choice of covariates in the equations is influenced by existing research (Kim & Lee, 2012; Treibich, 2015; Krause, 2019). Because of the count nature of the outcome variables, equation was estimated using Poisson regression models and marginal effects were reported.…”
Section: Methodsmentioning
confidence: 99%
“…A separate regression is run for each measure of diversification using the following estimating equations: (Kim & Lee, 2012;Treibich, 2015;Krause, 2019). Because of the count nature of the outcome variables, equation 1 was estimated using Poisson regression models and marginal effects were reported.…”
Section: Estimationmentioning
confidence: 99%
“…We found that married participants are more sensitive to matching contributions than their single counterparts. The reason for this may be that married participants may be more risk averse than their single counterparts and they evaluate matching contributions as a saving instrument with guaranteed yields [47].…”
Section: Participationmentioning
confidence: 99%